Factors Affecting Distribution Performance for Pharmaceutical Products in Kenya’s Public Sector - Achuora, John O.; Arasa, Robert M.; Nzioki, Wambwa; Ochiri, George; Muangangi, Patrick (International Journals of Multidisciplinary Research Academy, 2013)
This study examines the factors that affect distribution performance of pharmaceutical products in public sector in Kenya. It investigates the effect of financial capacity, transport outsourcing, third party relations and use of information technology on the distribution performance of KEMSA. The study uses sample survey for data collection through stratified random procedure for ensuring representativeness of the sample. Both quantitative and qualitative methods of data analysis are used. Descriptive statistics as well as correlation analysis are used for examining the relationship between variables of interest. The findings indicate that relations with government, donors and transport outsourcing followed by information technology and financial capacity have the greatest influence on distribution performance respectively. The finding of the study implies that information technology, transport outsourcing, relations with government and donors and financial capacity should be given due attention
Keywords: Information technology; Transport out sourcing; Relations with government and donors; Financial capacity; Distribution performance